Controle de Commelina benghalensis e Spermacoce densiflora por herbicidas alternativos ao glyphosate - Lima, Cauê Costa de (Universidade Federal de São Carlos, 2020)
The species Commelina benghalensis L. and Spermacoce densiflora have tolerance to the herbicide glyphosate and can be selected in places where the use of this herbicide is successive. Therefore, the objective of this work was to evaluate the effect of different herbicides on the control of these weeds in post-emergence at different phenological stages. The experimental design for each weed species studied was completely randomized in a 2 x 15 x 5 factorial scheme, with two weed phenological stages and 14 treatments involving the use of herbicides and 1 control without application, with 5 replications. The herbicides used will be: glyphosate (1,440 gi ha-1), glufosinate (500 g ia ha-1), 2,4-D (1,000 g ia ha-1), chlorimuron-ethyl (20 g ia ha-1 ), carfentrazone-ethyl (920 g ia ha-1), flumioxazin (50 g ia ha-1), s-metolachlor (960 g ia ha-1), saflufenacil (50 g ia ha-1). The applications were carried out separately in two different phenological stages: up to 4 pairs of leaves and up to 6 pairs of definitive leaves. The percentage of visual control was observed at 7, 14, 21, 28 and 35 days after application (DAA), and on that last date, the dry mass of the aerial part of the treated plants was measured. The data had their averages compared by the Tukey test at 5% of significance. Regarding the control, it was possible to observe in both species, that it was more significant when the application was carried out in the youngest phenological stages, in 4 pairs of leaves. In relation to the treatments, what was more effective for the species C. benghalensis L., in 6 pairs of leaves at 35 DAA were ammonium glufosinate, glyphosate + 2,4-D, but they did not present control above 90%, and for 4 pairs of leaves the treatments were ammonium glufosinate, carfentrazone, glyphosate + 2,4-D, glyphosate + carfentrazone, glyphosate + flumioxazin and glyphosate + saflufenacil. For S. densiflora, in the evaluation of 35 DAA in 6 pairs of leaves, the treatments glufosinate ammonium, gliphosate + flumioxazin and gliphosate + saflufenacil were the ones that showed better control, and for 4 pairs of leaves, it is added to this list the flumioxazin, glyphosate + chlorimuron-ethyl treatments. Regarding the control of sprouted plants, of the species Spermacoce densiflora, the only satisfactory treatment was the association of glyphosate with S-Metolachlor, maintaining an injury scale of approximately 90% in all evaluations, only at the youngest phenological stage, however, no control showed 100% efficiency.
Control of Commelina benghalensis and Spermacoce densiflora by herbicides alternative to glyphosate
Keywords: Tolerância; Herbicidas alternativos; Estadios fenológicos; Trapoeraba; Vassourinha de botão; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA